The Philosophical Legacy of Ibrohim Mominov: The Interconnection Between Spirituality and Culture - Begzod Yadgarov (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article analyzes the philosophical legacy of the Uzbek philosopher Ibrohim Mominov and his approach to understanding the interrelation between spirituality and culture. The article demonstrates how, in Mominov’s philosophy, spirituality and culture are conceptualized as mutually transformative and interrelated concepts. According to Mominov, spirituality and culture are interconnected and complementary elements, as they constitute the social and moral foundations of society. The article analyzes how Mominov’s philosophical perspectives have influenced the spiritual and cultural development of contemporary Uzbek society.